The Significance of Personality's Volied Qualities in Professional Development - Yuldashevich, Turdimurodov Dilmurod (International Journal on Orange Technologies, 2023)
In the structure of professionally important qualities, a special place is given to the volitional qualities of the individual. The manifestation of volitional qualities is determined not only by the motives of a person, his moral attitudes, but also by the innate features of the manifestation of the properties of the nervous system. The study and development of volitional qualities is of great importance for many types of activities, including professional activities of the individual.